Modelling, validation and roll moment rejection control of pneumatically actuated active roll control for improving vehicle lateral dynamics performance. (3rd August 2009) - Hudha, Khisbullah; Kadir, Zulkiffli Abd.; Said, Md. Radzai; Jamaluddin, Hishamuddin
This paper presents a detailed derivation of a full vehicle model and validation using an instrumented experimental vehicle. Two types of vehicle dynamics test are performed for the purpose of model validation namely step steer test and double lane change test. The results of model validation show that the behaviours of the model closely follow the behaviour of a real vehicle. An active roll control (ARC) suspension system is then developed on the validated full vehicle model to reduce unwanted vehicle motions during cornering manoeuvres. The proposed controller structure for the ARC system is PID control with roll moment rejection loop. The results of the study show that the proposed control structure is able to significantly improve the dynamics performance of the vehicle compared to the passive vehicle system. The additional roll moment rejection loop is able to further improve the performance of the PID controller for the ARC system.